Autophagy facilitates lung adenocarcinoma resistance to cisplatin treatment by activation of AMPK/mTOR signaling pathway - Wu T; Wang MC; Jing L; Liu ZY; Guo H; Liu Y; Bai YY; Cheng YZ; Nan KJ; Liang X (Dove Medical Press, 2015)
Tao Wu,1 Min-Cong Wang,1 Li Jing,1 Zhi-Yan Liu,2 Hui Guo,1 Ying Liu,3 Yi-Yang Bai,1 Yang-Zi Cheng,1 Ke-Jun Nan,1 Xuan Liang1 1Department of Medical Oncology, The First Affiliated Hospital of Xi’an Jiaotong University, 2Department of Respiratory Medicine, Xi’an Central Hospital, 3Department of Medical Oncology, Shaanxi Provincial People’s Hospital, Xi’an, Shaanxi, People’s Republic of China Abstract: Resistance to cisplatin-based therapy is a major challenge in the control of lung cancer progression. However, the underlying mechanisms remain largely unclear. Autophagy is closely associated with resistance to lung cancer therapy, but the function of autophagy in cisplatin treatment is still controversial. Here, we investigated whether autophagy was involved in lung adenocarcinoma resistance to cisplatin and further elucidated the underlying molecular mechanisms. Cisplatin-refractory lung adenocarcinoma cells increased autophagic vacuole formation detected by monodansylcadaverine staining. When exposed to cisplatin, lung adenocarcinoma cells demonstrated increased levels of autophagy detected by MAP1A/1B LC3B and mammalian homologue of yeast Atg6 (Beclin-1) expression using Western blot analysis. Activation of cisplatin-induced autophagic flux was increased by using chloroquine (CQ), which can accumulate LC3B-II protein and increase punctate distribution of LC3B localization. The combination of cisplatin with CQ was more potent than cisplatin alone in inhibiting lung adenocarcinoma cell growth, which also increased cisplatin-induced apoptosis. Compared to cisplatin treatment alone, the combination of cisplatin and CQ decreased p-AMPK and increased p-mTOR protein expressions, in addition, the AMPK inhibitor Compound C plus cisplatin downregulated p-AMPK and upregulated p-mTOR as well as depressed LC3B cleavage. These findings demonstrate that activation of autophagy is a hallmark of cisplatin exposure in human lung adenocarcinoma cells, and that there is a cisplatin-induced autophagic response via activation of the AMPK/mTOR signaling pathway. We speculate that autophagy can be used as a novel therapeutic target to overcome cisplatin-resistant lung adenocarcinoma. Keywords: autophagy, lung cancer, A549 cells, A549/DDP cells, chemoresistance, AMPK, chloroquine